2017
DOI: 10.1128/jvi.01755-16
|View full text |Cite
|
Sign up to set email alerts
|

Nonstructural Protein 4 of Porcine Reproductive and Respiratory Syndrome Virus Modulates Cell Surface Swine Leukocyte Antigen Class I Expression by Downregulating β2-Microglobulin Transcription

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) is the causative agent of PRRS, which has important impacts on the pig industry. PRRSV infection results in disruption of the swine leukocyte antigen class I (SLA-I) antigen presentation pathway. In this study, highly pathogenic PRRSV (HP-PRRSV) infection inhibited transcription of the ␤2-microglobulin (␤2M) gene (B2M) and reduced cellular levels of ␤2M, which forms a heterotrimeric complex with the SLA-I heavy chain and a variable peptide and plays a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Several signaling pathways, including the TLR signaling pathways and RIG‐I‐like receptor signaling pathway, are targeted by PRRSV, suggesting a complicated antagonism between the host and PRRSV. In addition, GO analysis revealed that the down‐regulated proteins were enriched in the GO term “antigen processing and presentation.” It is known that PRRSV infection impairs expression of swine leukocyte antigen complex on the cell surface, thereby modulating antigen presentation . We observed altered expression levels of MHC class II antigen, dynactin, and TAP2, which are involved in the antigen processing and presentation pathways, suggesting that PRRSV might utilize the secreted proteins to interference with the antigen processing and presentation processes through cell‐to‐cell communications.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Several signaling pathways, including the TLR signaling pathways and RIG‐I‐like receptor signaling pathway, are targeted by PRRSV, suggesting a complicated antagonism between the host and PRRSV. In addition, GO analysis revealed that the down‐regulated proteins were enriched in the GO term “antigen processing and presentation.” It is known that PRRSV infection impairs expression of swine leukocyte antigen complex on the cell surface, thereby modulating antigen presentation . We observed altered expression levels of MHC class II antigen, dynactin, and TAP2, which are involved in the antigen processing and presentation pathways, suggesting that PRRSV might utilize the secreted proteins to interference with the antigen processing and presentation processes through cell‐to‐cell communications.…”
Section: Discussionmentioning
confidence: 83%
“…Highly pathogenic PRRSV strain SH‐PRRS01 used in this study was propagated in PAMs and titered by 50% cell culture infectious dose (TCID 50 ) assay in Marc‐145 cells. PAMs were isolated from 30‐day‐old clinically healthy crossbred pigs raised in the animal facility of Shanghai Academy of Agricultural Sciences, Shanghai, China, as previously described . All animal experiments were approved by the Institutional Animal Care and Use Committee of Shanghai Veterinary Research Institute (IACUC No: Shvri‐Pi‐0124) and performed in compliance with the Guidelines on the Humane Treatment of Laboratory Animals (Ministry of Science and Technology of the People's Republic of China, Policy No.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HP-PRRSV nsp4 has greater inhibitory effect on IFNβ than nsp4 of less pathogenic strains. As discussed above, nsp1α binds to and degrades SLA-I (Du et al, 2016a), A recent study supports this finding that HP-PRRSV nsp4 also downregulates the cellular level of β2microglobulin (β2M) (Qi et al, 2017), which forms a heterotrimeric complex with the SLA-I heavy chain and plays a critica1 role in SLA-I antigen presentation. PRRSV nsp4 binds to the B2M promoter and suppresses β2M transcription.…”
Section: Suppression Of Type I Interferon Responsementioning
confidence: 62%
“…PRRSV nsp4 performs as a 3C-like main protease that has multiple functions in the virus life cycle (65)(66)(67)(68). It plays important roles in antagonizing host antiviral immunity and in the maturation of replicase polyproteins pp1a and pp1ab (65)(66)(67)(68)(69)(70). According to EAV replicase processing, PRRSV nsp4 was supposed to mediate 9 cleavages in the nsp3-to-nsp12 region (69,70).…”
Section: Insight Into the Interactions Of Nsp9 And Nsp10 With Membranmentioning
confidence: 99%